Laser welding of a Si-Al alloy - Quah, Kenneth Hong Yao (2015)
Due to the low coefficient of thermal expansion (CTE) and high wear resistance, Al-Si alloys are used in electronic packaging. However these Al-Si alloys are difficult to weld and attempts had been made to weld these alloys using laser welding. Severe defects occurred during the welding process which can have adverse effects on the mechanical properties of these alloys. Thus, it is important to understand how and why these defects were formed and ways to avoid these defects. The project is to examine the defects formed in both the welded zone and heat affected zones of a laser welded Si-Al alloy and to look into ways to avoid these defects. A sample of Al-Si alloy was given for observation using optical microscope to see the laser welding section before metallographic sample preparation of the alloy was carried out. Purpose of the metallographic sample preparation is to enable the microstruture of the Al-Si alloy to be clearly seen using both an optical microscope and scanning electron microscope (SEM). This will allow the laser welded section to be studied and defects that occurred during the welding process can be identified. The causes of the formation of these defects and ways to avoid these defects were studied as well. It can be seen that the defects were caused by the nature of aluminium in Al-Si alloy and the flaws of laser welding. These defects can be avoided or reduced to a large extent by pre-treatment of the Al-Si alloy and controlling the parameters used during laser welding. Laser welding aluminium alloys such as Al-Si alloy is a feasible form of welding provided the laser parameters were set in such a way that these defects can be largely avoided.